Craniofacial morphology in Turner syndrome karyotypes - Bajraktarova Miševska, Cvetanka; Kočova, Mirjana; Kanurkova, Lidija; Curcieva Cuckova, Gabriela; Bajraktarova, Bona; Maneva, Marija; Bajraktarova Valjakova, Emilija (South European Journal of Orthodontics and Dentofacial Research (SEJODR), 2017)
Introduction: A complete or partial absence of an X chromosome in the karyotype of phenotypic females has an impact on craniofacial morphology. The aim of this study was to determine the characteristics of the craniofacial complex in patients with Turner syndrome (TS), and to evaluate the influence of various karyotypes on craniofacial morphology.Materials and methods: The study population was comprised of 40 TS female patients, aged 9.2 to 18 years, and 40 healthy females,aged 9.3 to 18 years, as the control group. The TS patients were subdivided according to karyotype. All study participants were evaluated cephalometrically. An analysis of variance (ANOVA) and Tukey’s multiple comparison test were used for analysis of the differences between the means in Turner subgroups and the control group.Results: In general, the girls with TS were characterized by smaller dimensions and an altered morphology of the craniofacial complex compared with the unaffected girls. The curvature of the frontal bone was significantly increased, while the diameter of the head was reduced. Both the maxilla and mandible were retrognathic, posteriorly rotated, and reduced in antero-posterior length. The cranialbase was shorter and flattened. Among the different karoytypes, no significant differences were determined in the dimensions of the craniofacial complex in girls with TS.Conclusions: Our findings indicate that the karyo type has no effect on craniofacial morphology and we confirmed that a specific model of craniofacial morphology in individuals with TS is present in early childhood.